# SOLVING LINEAR EQUATIONS IN ONE VARIABLE

## About "Solving Linear Equations in One Variable"

Solving Linear Equations in One Variable :

A linear equation in one variable is any equation that can be written in the form

ax + b  =  0

where a and b are real numbers and x is a variable. This form is called standard form of a linear equation in one variable.

But, all the linear equations in one variable can not be expected to be in this form. Always we can not expect x as variable and we may have some other English alphabet as variable.

In this section, we are going to learn, how to solve linear equations in one variable. That is, how to find the value of the variable.

## Solving Linear Equations inn One Variable - Key Concept

To solve linear equations in one variable, we have to isolate the variable x. That is, we have to get rid of all the values around the variable.

## Solving Linear Equations inn One Variable - Rules

Rule 1 :

Simplify each side of the equation, if needed.

Rule 2 :

An equal quantity may be added to each side of the equation.

Rule 3 :

An equal quantity may be subtracted from each side of the equation.

Rule 4 :

An equal, non-zero quantity may multiply each side of the equation.

Rule 5 :

An equal, non-zero quantity may divide each side of the equation.

## Solving Linear Equations inn One Variable - Examples

Example 1 :

Solve for x :

x - 3  =  2

Solution :

To solve for x, add 3 to each side of the equation.

x - 3 + 3  =  2 + 3

x  =  5

Example 2 :

Solve for x :

3x - 2(x - 1)  =  5

Solution :

Simplify the left side of the equation.

3x - 2(x - 1)  =  5

3x - 2x + 2  =  5

Combine the like terms.

x + 2  =  5

Subtract 2 from each side of the equation.

x + 2 - 2  =  5 - 2

x  =  3

Example 3 :

Solve for x :

3x - 8  =  x + 10

Solution :

Subtract x from each side of the equation.

3x - 8 - x  =  x + 10 - x

Combine the like terms.

2x - 8  =  10

Add 8 to each side of the equation.

2x - 8 + 8  =  10 + 8

2x  =  18

Divide each side by 2.

2x / 2  =  18 / 2

x  =  9

Example 4 :

Solve for x :

5(x - 3) - 7(6 - x)  =  24 - 3(8 - x) - 3

Solution :

Simplify each side of the equation.

5(x - 3) - 7(6 - x)  =  24 - 3(8 - x) - 3

5x - 15 - 42 + 7x  =  24 - 24 + 3x - 3

Combine the like terms.

12x - 57  =  3x - 3

Subtract 3x from each side of the equation.

12x - 57 - 3x  =  3x - 3 - 3x

9x - 57  =  - 3

Add 57 to each side of the equation.

9x - 57 + 57  =  - 3 + 57

9x  =  54

Divide each side by 9.

9x / 9  =  54 / 9

x  =  6

Example 5 :

Solve for x :

4x/5 - 7/4  =  x/5 + x/4

Solution :

In the given equation, we have the denominators 4 and 5. The least common multiple of 4 and 5 is 20.

Now, we can proceed as follows.

4x/5 - 7/4  =  x/5 + x/4

16x/20 - 35/20  =  4x/20 + 5x/20

(16x - 35)/20  =  (4x + 5x)/20

(16x - 35)/20  =  9x/20

Multiply each side by 20.

20 ⋅ [(16x - 35)/20]  =  (9x/20) ⋅ 20

16x - 35  =  9x

Subtract 9x from each side.

16x - 35 - 9x  =  9x - 9x

7x - 35  =  0

7x - 35 + 35  =  0 + 35

7x  =  35

Divide each side by 7.

7x / 7  =  35 / 7

x  =  5

Example 6 :

Solve for x :

4x/3 - 1  =  14x/15 + 19/5

Solution :

Simplify each side of the equation.

4x/3 - 1  =  14x/15 + 19/5

4x/3 - 3/3  =  14x/15 + 57/15

(4x - 3) / 3  =  (14x + 57) / 15

Least common multiple of 3 and 15 is 15. So, multiply each side of the equation by 15.

15 ⋅ [(4x - 3) / 3]  =  15 ⋅ [ (14x + 57) / 15 ]

Simplify.

(4x - 3)  =  14x + 57

20x - 15  =  14x + 57

Subtract 14x from each side of the equation.

20x - 15 - 14x  =  14x + 57 - 14x

6x - 15  =  57

Add 15 to each side of the equation.

6x - 15 + 15  =  57 + 15

6x  =  72

Divide each side by 6.

6x / 6  =  72 / 6

x  =  12

Example 7 :

The denominator of a fraction exceeds the numerator by 2. If 5 be added to the numerator, the fraction increases by unity. Find the fraction.

Solution :

Let x be the numerator of the fraction.

Then the fraction is

x / (x + 2) -----(1)

Given : If 5 be added to the numerator, the fraction increases by unity.

(x + 5) / (x + 2)  =  [x / (x + 2)] + 1

Simplify.

(x + 5) / (x + 2)  =  [x / (x + 2)] + [(x + 2) / (x + 2)]

(x + 5) / (x + 2)  =  (x + x + 2) / (x + 2)

Multiply each side by (x + 2).

x + 5  =  2x + 2

Subtract x from each side.

x + 5 - x  =  2x + 2 - x

5  =  x + 2

Subtract 2 from each side.

5 - 2  =  x + 2 - 2

3  =  x

Plug x  =  3 in (1).

(1)----->  x / (x + 2)  =  3 / (3 + 2)

x / (x + 2)  =  3 / 5

Hence, the required fraction is 3/5.

Example 8 :

Three consecutive integers add up to 51. What are these integers?

Solution :

Let x be the first integer.

Then the remaining two consecutive integers are

(x + 1) and (x + 2)

So, the three consecutive integers are

x, (x + 1), and (x + 2)

Given : Three consecutive integers add up to 51.

So, we have

x + (x + 1) + (x + 2)  =  51

x + x + 1 + x + 2  =  51

Combine the like terms.

3x + 3  =  51

Subtract by 3 from each side side.

3x + 3 - 3  =  51 - 3

3x  =  48

Divide each side by 3.

3x / 3  =  48 / 3

x  =  16

Hence, the three consecutive integers are 16, 17 and 18.

After having gone through the stuff given above, we hope that the students would have understood, "Solving Linear Equations in One Variable".

Apart from the stuff given in this section if you need any other stuff in math, please use our google custom search here.

You can also visit our following web pages on different stuff in math.

WORD PROBLEMS

Word problems on simple equations

Word problems on linear equations

Algebra word problems

Word problems on trains

Area and perimeter word problems

Word problems on direct variation and inverse variation

Word problems on unit price

Word problems on unit rate

Word problems on comparing rates

Converting customary units word problems

Converting metric units word problems

Word problems on simple interest

Word problems on compound interest

Word problems on types of angles

Complementary and supplementary angles word problems

Double facts word problems

Trigonometry word problems

Percentage word problems

Profit and loss word problems

Markup and markdown word problems

Decimal word problems

Word problems on fractions

Word problems on mixed fractrions

One step equation word problems

Linear inequalities word problems

Ratio and proportion word problems

Time and work word problems

Word problems on sets and venn diagrams

Word problems on ages

Pythagorean theorem word problems

Percent of a number word problems

Word problems on constant speed

Word problems on average speed

Word problems on sum of the angles of a triangle is 180 degree

OTHER TOPICS

Profit and loss shortcuts

Percentage shortcuts

Times table shortcuts

Time, speed and distance shortcuts

Ratio and proportion shortcuts

Domain and range of rational functions

Domain and range of rational functions with holes

Graphing rational functions

Graphing rational functions with holes

Converting repeating decimals in to fractions

Decimal representation of rational numbers

Finding square root using long division

L.C.M method to solve time and work problems

Translating the word problems in to algebraic expressions

Remainder when 2 power 256 is divided by 17

Remainder when 17 power 23 is divided by 16

Sum of all three digit numbers divisible by 6

Sum of all three digit numbers divisible by 7

Sum of all three digit numbers divisible by 8

Sum of all three digit numbers formed using 1, 3, 4

Sum of all three four digit numbers formed with non zero digits

Sum of all three four digit numbers formed using 0, 1, 2, 3

Sum of all three four digit numbers formed using 1, 2, 5, 6